The top 5 can't-miss sport supplements - Antonio, J.; Pereira, A. J.; Curtis, J.; Rojas, J.; Evans, C. (Nutrients, 2024)
Background/Objectives Sports supplements have become popular among fitness enthusiasts for enhancing the adaptive response to exercise. This review analyzes five of the most effective ergogenic aids: creatine, beta-alanine, nitrates, caffeine, and protein.